Effects of 2, 4-thiazolidinedione (TZD) on milk fatty acid profile and serum vitamins in dairy goats challenged with intramammary infusion of Streptococcus uberis. Issue 4 (10th November 2020) - Tsai, Chia-Yu; Rosa, Fernanda; Bionaz, Massimo; Rezamand, Pedram
Abstract: The study included two experiments. In the first, 24 lactating Saanen dairy goats received low-energy diet without vitamin supplements. Twelve goats received a daily IV injection of 2, 4- thiazolidinedione (TZD), others received saline injection. A week later, 6 goats from each treatment were challenged with intramammary infusion (IMI) of saline (CTRL) or Streptococcus uberis . In the second experiment, 12 Saanen lactating dairy goats received supplemental vitamins to reach NRC recommendation level. Six goats in each group were injected with TZD or saline daily, and 14 d later received Streptococcus uberis IMI in the right half of the udder. The hypotheses were (1) TZD does not affect the level of retinol in blood, and (2) the fatty acid profile is affected by the interaction between mammary infection and TZD in dairy goats. In the first experiment blood samples were collected on d −7, −2, 1, 2, 12 and milk samples were collected on d −8, 1, 4, 7, and 12, both relative to IMI. In the second experiment, blood samples were collected on d −15, 0, 1, and 10 relative to IMI. Milk and serum samples were analyzed for retinol, α-tocopherol and fatty acid profile. Serum retinol and β-carotene concentrations were higher in the second experiment compared to the first. Serum β-carotene and α-tocopherol were greater in TZD than CTRL and there was a TZD × time interaction in the first experiment. In addition, the TZD × time interaction showed that the milk fatty acid were reduced in C16 : 0 while C18 : 3 n3 while total omega 3 fatty acids were increased, as well as with minor effect on preventing a transient increase in α-tocopherol in milk. Overall, the TZD may affect the lipid-soluble vitamins and fatty acid profile, potentially altering immune responses, during mastitis in dairy goats.